KAJIAN FAKTOR EKSPLOITASI BERDASARKAN JENIS POHON : STUDI KASUS DI SATU PERUSAHAAN HPH DI KALIMANTAN BARAT (A study on Exploitation Factor in Forest Harvesting Based on Trees Species : A case study in one forest concession holder in West Kalimantan) - Wesman Endom; Maman Mansyur Idris (Pusat Penelitian dan Pengembangan Hasil Hutan, 1996)
Natural production forests in Indonesia have been harvested since 1970. In carrying out the harvesting of the forests, the goverment used a parameter so called Exploitation Factor (FE) as a basic calculation of annual allowable production. Currently the value of FE is 0. 7 regardless the species. The value means that only about 70% of log volume can be extracted from the forest in the cutting operation.In this study an analysis of FE was carried out to see whether it is necessary to differentiate the value based on tree species. Data were collected from real logging activity in the forest. An analysis using Honest by Significant Difference test showed that in reality there is no signifi cant difference among the means of FE. This result justifies the use of single value of FE for all species.Keywords: Forest, harvesting, logs, conversion factor.